Demonstrating an approach for modeling crop growth and hydrology using SWAT 2009 in Kanopolis Lake Watershed, Kansas - Mollenkamp, Lorinda Larae (Kansas State University, 2013)
According the U.S. Environmental Protection Agency’s (EPA) website, our planet is at risk of global warming due to greenhouse gas emissions. The earth’s average temperature has been reported to have risen by 1.4°F over the last century. This seemingly small increase in average planetary temperature has been linked to devastating floods, severe heat waves, and dangerous and unpredictable shifts in our climate (US EPA, 2013a). In the 2012 report, the Intergovernmental Panel on Climate Change states that bioenergy has the potential to significantly mitigate greenhouse gases as long as this is produced in a sustainable manner (Chum, et al., 2011). In light of these facts, research into the sustainable production of bioenergy sources in the United States is currently underway. To ensure that the correct biofuel crop is selected for a given region and to investigate any secondary effects of changing our nation’s agricultural practices to include biofuels, computer models can be very useful. The Soil Water Assessment Tool (SWAT) is a robust, continuous time step model that was developed by the USDA Agricultural Resource Service that can simulate changes in land use and land management and the effect this has on erosion, water quality, and other important factors. This paper describes the preliminary work to create a model of the Kanopolis Lake Watershed that is part of the Kansas River Basin using SWAT 2009. Data pertaining to weather, topography, land use, management, stream flow, and reservoirs was gathered and incorporated into the SWAT model. This was then simulated to obtain the uncalibrated data. SWAT produced unacceptable statistics for both crop yields and for stream flow using the Nash-Sutcliffe Efficiency equation and using percent bias. This suggests that the model must be calibrated to be of use in understanding both the current and future land use scenarios. Once the model is calibrated and validated, it can be used to simulate different biofuel cropping scenarios.
Keywords: Soil Water Assessment Tool; Agricultural watershed; Stream flow; Crop growth; Engineering (0537); Engineering, Agricultural (0539); Environmental Engineering (0775)